THE EXPOSURES OF SCOTTISH CULTURE IN DIANA GABALDON’S OUTLANDER - KARDA, NI MADE FANY RENJANA (Jurnal Ilmiah Mahasiswa FIB, 2015)
Keywords: Culture, Scotland, Outlander, novel.Culture and society are related to each other and inseparable. Based on Koentjaraningrat (2009), culture consists of seven elements called Cultural Universal.That is, culture appears in every country around the world, including in Scotland. Theproblem of this study is on how Scottish culture is exposed in a novel.This study aims to find out the culture of Scotland in Diana Gabaldon’s novel entitled Outlander. This novel tells about the experience of an English woman named Claire Randal Fraser when she lives in Scotland. To support the analysis, sociological approach to literature about the theory of culture is applied. This theory is used toanalyze the elements of Scottish culture appear in the novel.Since the main character of this novel experienced the culture of Scotland, the result of this study shows that the culture of Scotland is mostly influenced by the culture of Celtic. The elements of culture are reflected in the novel are the Gaelicspeaking of the people of Scotland, the local genius of Scottish ancient medication, the leadership system of a Scottish clan, the necessities shared by the people of Scotland including the house, food beverages and the clothing, the Quarter Days as farming system of Scotland, the rituals and superstitions shared by the people as the belief system, and the folktales that are handed through generations.In conclusion, the culture of Celtic influences Scottish culture from the language, medication, necessities of Scottish people, farming system, superstitions and rituals, and the folktales. English culture also influences Scottish culture in the clan system. The other researchers need to do further studies in the novel Outlander by exploring the novel with historical approach to expose deeper about the history of Scotland.